The Protection Relay Coordination Studies (Over Current Relays and Ground Fault Relays) On The Power Plant Electrical System, PT. Rekind Daya Mamuju By Using The ETAP 12.6 Program - Firdaus Firdaus; Andi Imran; Fatma S; Syarifuddin Kasim (Muhammadiyah University, Sidoarjo, 2023)
This research is an ex-post facto descriptive study, which aims to determine: a) the results of the safety relay coordination settings (OCR and GFR) and b) the working sequence and operating time of the safety relay when a disturbance occurs in the electrical system of PT. Rekind Daya Mamuju. Electrical system data obtained in the form of Single Line Diagram of PLTU Mamuju 2x25 MW, protection equipment data, and safety relay coordination data which are then processed and analyzed using the ETAP 12.6 program. The results showed that on the OCR inverse time curve the secondary side of the 0.4 kV transformer is set with a pickup current of 0.45 s, the primary side relay of the transformer is 6.3 kV 0.25 s and the relay is connected between unit I and unit II. 0.84 s. The GFR setting value for the definite time curve for the secondary side of the pickup current is 0.4 s, and the relay on the primary side is 0.2 s. The working time interval of the relay to break the disturbance is 0.3 s. Coordination of safety relays for PLTU Mamuju unit I and Unit II has worked well, with no overlapping or miss-coordination curve plot values. The sequence of work and the time of operation of the relay when a disturbance occurs is in the order of the simulation results with the coordinated setting values.